Luwuk Muhammadiyah High School Students' Entrepreneurship Capability - Irwan Moridu; Fitriani Fitriani; Nurcahya Hartaty Posumah; Debiyanti Kune; Yusni Yusni (Universitas Kristen Indonesia Toraja, 2023)
Communication training is a common sort of education, particularly in the business world. The purpose of this exercise is to assist SMA Muhammadiyah Luwuk students in developing their business skills. The problem is that students do not have access to entrepreneurship education communication resources at school. The training method is divided into four stages: displaying a video about the significance of communication, offering material and business communication simulations for communication skills training, and drawing conclusions from all of the training supplied. The results of the corporate communication training program have helped SMA Muhammadiyah students improve their communication skills and gain confidence in public speaking.